2015
DOI: 10.1515/ijamh-2014-0041
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of smoking initiation among school students in Bosnia and Herzegovina

Abstract: This study indicates that a high proportion of 15-18 year olds in the town of Zvornik are current smokers. Gender, age, and parent and peer influence were identified as important associations with smoking. Interventions should not only be confined to the secondary school environment but they should also extend to their places of residence so that influences in the home environment and social surroundings that contribute to tobacco use are also tackled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Several other risk behaviors usually emerge during early adolescence and tend to cluster with tobacco use such as substances use, mental health problems, risky sexual behavior, injury risk behavior like motor vehicle accidents and acts of violence in addition to sedentary behavior and unhealthy eating habits [ 2 , 3 , 9 ]. The gateway effect of tobacco in addition to common socio-cultural and psycho-pathological risk factors may be behind these risk behaviors [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several other risk behaviors usually emerge during early adolescence and tend to cluster with tobacco use such as substances use, mental health problems, risky sexual behavior, injury risk behavior like motor vehicle accidents and acts of violence in addition to sedentary behavior and unhealthy eating habits [ 2 , 3 , 9 ]. The gateway effect of tobacco in addition to common socio-cultural and psycho-pathological risk factors may be behind these risk behaviors [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, students having smoking friends, seeing school personnel smoking on the school premises, perceiving smoking girls more attractive, and no school training on tobacco harm were also factors of smoking susceptibility. Racic et al also identified the determinants of smoking initiation among high school students [3]. About 45% of fourth-grade students initiated smoking, which was higher than second-and third-grade students.…”
mentioning
confidence: 99%